INFLUENCE OF LIQUIDITY, SOLVENCY AND PROFITABILITY ON COMPANY PROFIT GROWTH (Case Study: Against Printing, Advertising and Media Sector Companies, 2016-2020) - Dini Marse Herminda; Deddi Nordiawan; Yunni Rusmawati DJ (Sean Institute, 2023)
This study aims to determine the effect of Liquidity, Solvency and Profitability on Profit Growth in the Company. The purpose of this study was to determine the relationship between Current Ratio, Debt to Equity Ratio, and Net Profit Margin partially, simultaneously and with determination. Sample of 10 companies with purposive sampling method. Data analysis using SPSS.20 Software. The results of this study CR and NPM do not have a partially significant effect, while DER has an effect. All independent variables have simultaneous effect on the dependent variable. The value of determination is 85.8%.